2001
DOI: 10.1523/jneurosci.21-01-00270.2001
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalar Efferents Initiate Auditory Thalamic Discriminative Training-Induced Neuronal Activity

Abstract: It is well known that neurons of the medial geniculate (MG) nucleus of the thalamus send axonal projections to the amygdala. It has been proposed that these projections supply information that supports amygdalar associative processes underlying acquisition of acoustically cued conditioning and learning. Here we demonstrate the reverse direction of influence. Temporary inactivation of the amygdala using the GABA A receptor agonist muscimol just before the onset of discriminative avoidance conditioning permanent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 59 publications
8
64
1
Order By: Relevance
“…Other investigators (Bahar et al 2003) reported that local blockade of ␤-adrenergic receptors in the CeA blocks acquisition but not extinction of CTA, and a similar intervention in the BLA blocks extinction but not acquisition. Furthermore, recent findings indicate that the BLA regulates the development of learning-induced plasticity in the medial geniculate nucleus (Maren et al 2001;Poremba and Gabriel 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators (Bahar et al 2003) reported that local blockade of ␤-adrenergic receptors in the CeA blocks acquisition but not extinction of CTA, and a similar intervention in the BLA blocks extinction but not acquisition. Furthermore, recent findings indicate that the BLA regulates the development of learning-induced plasticity in the medial geniculate nucleus (Maren et al 2001;Poremba and Gabriel 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies report that plasticity in the MGm is dependent on the amygdala, although there are no reciprocal geniculo-amygdala projections 79,80 . However, these studies inactivated the amygdala with muscimol, which has physiological effects for several millimetres around the injection site 81 .…”
Section: Loci Of Plasticitymentioning
confidence: 99%
“…In summary, available evidence strongly suggests that Hebbian neural changes occur in LA during fear conditioning, and these changes are critical for the conditioning of fear responses to an auditory CS. Although LA may not be the only site of such changes (e.g., Weinberger 1995;Maren et al 2001;Poremba and Gabriel 2001), it is very likely a site where changes relevant to behavioral fear learning occur. We now discuss synaptic events that might underlie these neural changes in LA.…”
Section: Blair Et Almentioning
confidence: 99%